THE ANCIENT CIVILIZATIONS ON THE TERRITORY OF UZBEKISTAN - Gaybullayeva , Zilola; Majitova , Umriniso (Effective scientific journals, 2025)
This article provides a comprehensive analysis of the ancient civilizations that emerged on the territory of modern Uzbekistan from early historical periods. The study examines the development of major ancient cultures such as Bactria, Sogdiana, Khorezm, and the civilizations of the Fergana Valley, highlighting their political organization, economic activities, and cultural achievements. Based on archaeological evidence, written sources, and scholarly research, the article demonstrates that this region played a crucial role as a center of early civilization and as a bridge connecting Eastern and Western cultures. Particular attention is given to urban development, craftsmanship, trade relations, irrigation systems, and the formation of religious and cultural beliefs. The influence of the Great Silk Road on the prosperity and interaction of these civilizations is also analyzed. The article emphasizes the significant contribution of ancient civilizations of Uzbekistan to world history and cultural heritage.